Developing banking system stability index for Nigeria - Angela Sere-Ejembi; Ini S. Udom; Audu Salihu; Ngozi V. Atoi; Baba N. Yaaba (CBN Journal of Applied Statistics, 2014)
This study constructed a banking system stability index (BSSI) for Nigeria, using a combination of financial soundness indicators and macro-fundamentals. It applied statistical and Conference Board Methodology normalisation processes on Nigeria's banking and macroeconomic data from 2007Q1 to 2012Q2. The resultant index traced fairly well the episodes of crisis in the system over the study period. Hence, the BSSI is capable of acting as an early warning mechanism of signaling fragility. It could, therefore, be used as a complimentary regulatory policy tool to detect potential threat to enable monetary authorities take timely pre-emptive policy measures to avert crisis.
Keywords: E58; G01; G17; E65; 330; Banking system; stability index; macro-prudential analysis; financial soundness indicators